2004
DOI: 10.1111/j.1365-3156.2004.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating concentrations of cardiac proteins in complicated and uncomplicated Plasmodium falciparum malaria

Abstract: SummaryIn an unmatched case-control study of 63 non-immune European patients with uncomplicated (n ¼ 52) and complicated (n ¼ 11) falciparum malaria, serum levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), heart-type fatty acid-binding protein (H-FABP), myoglobin, troponin T and creatin kinase-muscle brain were compared. Elevated levels of NT-proBNP and H-FABP indicated myocardial impairment in complicated but not in uncomplicated falciparum malaria. The clinical impact of these findings remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 20 publications
9
43
2
Order By: Relevance
“…This is especially true for myocardial impairment that has recently been demonstrated by our group. Indeed, we have found elevated levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) and heart-type fatty acid-binding protein (H-FABP) in complicated malaria cases, indicating myocardial impairment [15]. Children suffering from severe malaria exhibited high levels of cardiac markers.…”
Section: Discussionmentioning
confidence: 98%
“…This is especially true for myocardial impairment that has recently been demonstrated by our group. Indeed, we have found elevated levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) and heart-type fatty acid-binding protein (H-FABP) in complicated malaria cases, indicating myocardial impairment [15]. Children suffering from severe malaria exhibited high levels of cardiac markers.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the mechanism of bnp induction is independent on molecules secreted by leukocytes. The bnp up-regulation after 48 h might be related to the elevated levels of circulating BNP found in the serum of malaria patients [2,3]. A recent study has shown that BNP alone is not able to induce cardiomyocyte apoptosis in vitro but BNP increases the percentage of apoptotic cardiomyocytes due to mild hypoxia [22].…”
Section: Discussionmentioning
confidence: 96%
“…Ehrhardt et al [2,3] recently demonstrated cardiac impairment as one potential lethal complication besides cerebral malaria and anemia during P. falciparum infection. Elevated levels of BNP in vivo indicated a myocardial decompensation and were correlated with lactic acidosis and hypoglycemia in the infected patients [2,3]. The GPI of P. falciparum administered in mice is known to induce lactic acidosis and hypoglycemia [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), a sensitive marker of left ventricular dysfunction, have been shown to be elevated in patients presenting with severe malaria. 43 Parasite toxins, host immune mediators, metabolic acidosis, and decreased NO levels have all been implicated as causative for direct myocardial dysfunction. Conduction defects and nonspecific electrocardiogram abnormalities can occur, particularly in patients on quinine therapy.…”
Section: Cardiacmentioning
confidence: 99%